2012
DOI: 10.1177/000348941212100205
|View full text |Cite
|
Sign up to set email alerts
|

Parotidectomy: A 17-Year Institutional Experience at a Rural Academic Medical Center

Abstract: In this 17-year rural case series of all parotidectomy procedures done for nontrauma indications, the largest number of malignancies came from metastatic tumors. Although facial nerve paralysis is not a common complication, it occurs most often when surgery is performed for either primary or metastatic malignancy. Surgeons will benefit from this information as they counsel patients who are considering parotidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
15
2
Order By: Relevance
“…14,29 In this study, the Clavien-Dindo classification system, validated and tested for interobserver variation, made it possible to uniformly classify the severity and nature of complications. 31,32 They show complication rates between 10% and 24% (excluding facial nerve paralysis), however, these results are difficult to compare to the results in this study because of the different nature of the pathology. 30 Studies on postoperative complications after parotid surgery is mostly performed on patients with benign lesions.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…14,29 In this study, the Clavien-Dindo classification system, validated and tested for interobserver variation, made it possible to uniformly classify the severity and nature of complications. 31,32 They show complication rates between 10% and 24% (excluding facial nerve paralysis), however, these results are difficult to compare to the results in this study because of the different nature of the pathology. 30 Studies on postoperative complications after parotid surgery is mostly performed on patients with benign lesions.…”
Section: Discussioncontrasting
confidence: 60%
“…30 Studies on postoperative complications after parotid surgery is mostly performed on patients with benign lesions. 31,32 They show complication rates between 10% and 24% (excluding facial nerve paralysis), however, these results are difficult to compare to the results in this study because of the different nature of the pathology.…”
Section: Discussioncontrasting
confidence: 60%
“…Sialocele was reported in 102 studies 10,14,15,17,23,25,33–36,38,39,41–44,46,48,50,51,56–62,64,66,67,69,70,72–77,79–85,87–90,92,95,96,98,100–103,106–108,110–116,118–121,125,128,135–138,141,144,146,147,150–169 reporting on 13,760 patients (Table I and Fig. 2C).…”
Section: Resultsmentioning
confidence: 97%
“…Some risk factors for facial nerve weakness after parotidectomy have been considered in the literature,[ 58 ] such as pathological entity, age, gender, and secondary surgery. A recent review of 334 patients conducted by Maddox et al, [ 59 ] they reported that malignant tumors have been considered as a risk factor associated with a higher incidence of postoperative nerve dysfunction. The malignant parotid tumors characterized by infiltrating of the neighboring structures such as facial nerve and skin, and metastasized to the neck lymph nodes.…”
Section: Discussionmentioning
confidence: 99%